Correlation of Alcohol Use Disorders with Common Mental Disorders and Its Association with Socio-demographic Characteristics Among Community in Ethiopia: A Cross-sectional Study - Abdu Z; Hajure M (Dove Medical Press, 2020)
Zakir Abdu, Mohammedamin Hajure Department of Psychiatry, Faculty of Health and Medical Sciences, Mettu University, Mettu, EthiopiaCorrespondence: Zakir Abdu Tel +251 (0) 913845371Email zakirabdu45@gmail.comBackground: Alcohol use disorders occurring together with common mental disorders are common and have been recognized worldwide as a crucial public health concern. However, there is a scarcity of data about the correlation of alcohol use disorders with common mental disorders and its association with socio-demographic characteristics among community in Ethiopia, especially in the study area. The aim of the study is to assess the correlation of alcohol use disordesr with common mental disorders and its association with socio-demographic characteristics among adults of selected woredas of the Ilu Aba Bor zone.Methods: Community-based cross-sectional study was employed on 690 participants selected by using the multistage sampling technique. Data were collected by using the alcohol use disorder identification test (AUDIT) and self-reporting questionnaire (SRQ-20) scale. Data analysis were done using SPSS version 20. Pearson correlation was used to see the relation of two variables. The strength of the association was determined at p-value < 0.005.Results: 14.1% of the study sample positive for alcohol use disorders and 27.2% for common mental disorders. There is a significant positive relationship between alcohol use disorders and common mental disorders, r(688)=0.314, p=0.001. From socio-demographic characteristics, multivariable logistic regression analysis revealed marital status being single, orthodox religion followers, and living in urban had a significant association with alcohol use disorders.Conclusion: In the Ilu Aba Bor zone, 14.1% of participants reported alcohol use disorders, and 27.2% have a common mental disorders. There is a significant positive relationship between alcohol use disorders and common mental disorders. Being single, orthodox religion, and living in urban had a significant association with alcohol use disorders. Detection and treatment of people with alcohol use disorders and common mental disorders in the community have been recommended at the same time through integrated treatment.Keywords: alcohol use disorders, common mental disorders, Ilu Aba Bor